2022
DOI: 10.1186/s42494-022-00102-3
|View full text |Cite
|
Sign up to set email alerts
|

Case report of antiseizure medicine-induced long QT syndrome and a literature review

Abstract: Background To realize the clinical characteristics of long QT syndrome (LQTS) caused by antiseizure medicines (ASMs), and to improve the prevention and management of ASM-acquired QT syndrome. Case presentation A case of ASM-acquired QT syndrome was diagnosed and relevant literature was reviewed. The case was a 7-year-old boy who presented with a sudden onset of panic followed by changes in consciousness, with or without convulsions, lasting from te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
0
0
Order By: Relevance
“…However, there have been multiple case reports documenting levetiracetam-induced hypokalemia and hypomagnesemia [ 3 , 8 - 9 ]. Additionally, a literature review published in 2022 found twelve case reports and two studies that reported a prolonged QT interval caused by levetiracetam [ 10 ]. One case report reported torsades de pointes in a 24-year-old female with undiagnosed long QT syndrome who had her levetiracetam dose increased [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been multiple case reports documenting levetiracetam-induced hypokalemia and hypomagnesemia [ 3 , 8 - 9 ]. Additionally, a literature review published in 2022 found twelve case reports and two studies that reported a prolonged QT interval caused by levetiracetam [ 10 ]. One case report reported torsades de pointes in a 24-year-old female with undiagnosed long QT syndrome who had her levetiracetam dose increased [ 11 ].…”
Section: Discussionmentioning
confidence: 99%